Energy Potential Evaluation of Agroindustrial Waste - Silva, Maria Fernanda Felippe [UNESP]; da Silva, Nicole Santos [UNESP]; Silva, João Vítor Felippe [UNESP]; Caraschi, José Cláudio [UNESP]; Luna, Carlos Manuel Romero [UNESP]; de Campos, Cristiane Inácio [UNESP]; da Silva Viana, Ronaldo [UNESP] (Sociedade Brasileira de Quimica (SBQ), 2022)
Biomass has great potential for energy production, due to its renewability and low cost. The use of biomass as an energy source has intensified in Brazil, especially the use of agro-industrial waste. For a more appropriate use and the valorization of these residues it is necessary the knowledge of the chemical composition, which directly influences the energetic levels of biofuels. The main characteristics are the volatile matter and the High Heating Value (HHV). The aim of this paper was to evaluate the energy potential of agro-industrial waste through volatile matter and its HHV. The residues were soybean hull, peanut hull, sugar cane bagasse, sweet sorghum bagasse and tomato processing residue, which were compared with sawdust from Pinus sp. and Eucalyptus saligna. The HHV tests and volatile matter were performed according to the ASTM E 711-87 (2004) and E 872-82 (2013) standards, respectively. Results showed that the value of HHV of the residues varies from 18,418 to 24,844 ° MJ ° kg-1, as for the immediate analysis, the found values in the test of volatile materials and the fixed carbon content were close to pine and eucalyptus wood. Among the studied agro-industrial residues, the tomato-processing residue stood out due to its higher HHV. However, all residues indicate technical feasibility of using it for energy production.
Avaliação do Potencial Energético de Resíduos Agroindustriais
Keywords: high heating value; Vegetal biomass; volatile matter